Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1097/sla.0000000000003586
|View full text |Cite
|
Sign up to set email alerts
|

Casting A Wide Net On Surgery

Abstract: Since their discovery, neutrophil extracellular traps (NETs) have been implicated in a broad array of functions, both beneficial and detrimental to the host. Indeed, NETs have roles in infection, sepsis, wound healing, thrombotic disease, and cancer propagation, all of which are directly implicated in the care of surgical patients. Here we provide an updated review on the role of NETs in the perioperative period with specific emphasis on perioperative infections, wound healing, vascular complications, cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 77 publications
0
52
0
Order By: Relevance
“…Cause a dramatic reduction in thrombus deposition in mouse lungs [128] TLR4 inhibitor C34 Reduce systemic inflammation in the mouse models of endotoxemia [132] TAK-242 Suppress inflammation by combining with cysteine 747 existing in the TIR domain of TLR4, but fail to reduce cytokine levels in patients with sepsis [134,135] Eritoran Inhibit LPS-induced NF-κB activation and inflammatory cytokine production in vitro and animal models, but do not reduce 28-mortality among patients with severe sepsis [136][137][138] Degrade DNA DNase1 Preferentially cleave protein-free DNA and degrade the scaffold of NET structures [143] DNase1-like 3 Preferentially cleave DNA-protein complexes and degrade the scaffold of NET structures [143] NET-inhibitory factor nNIF and NRPs Block NET formation in vitro and mouse models of infection and systemic inflammation, and show improved prognosis in these models [144] Inhibit excessive glycolysis PFKFB3 blockade 3PO Protect mice from acute lung injury via suppression of NF-κB-mediated vascular inflammation [77] PFK158 Suppress ATP production and proliferation in the mouse models of small cell lung cancer [149] Phenoxyindole 44…”
Section: Gsk484mentioning
confidence: 99%
See 1 more Smart Citation
“…Cause a dramatic reduction in thrombus deposition in mouse lungs [128] TLR4 inhibitor C34 Reduce systemic inflammation in the mouse models of endotoxemia [132] TAK-242 Suppress inflammation by combining with cysteine 747 existing in the TIR domain of TLR4, but fail to reduce cytokine levels in patients with sepsis [134,135] Eritoran Inhibit LPS-induced NF-κB activation and inflammatory cytokine production in vitro and animal models, but do not reduce 28-mortality among patients with severe sepsis [136][137][138] Degrade DNA DNase1 Preferentially cleave protein-free DNA and degrade the scaffold of NET structures [143] DNase1-like 3 Preferentially cleave DNA-protein complexes and degrade the scaffold of NET structures [143] NET-inhibitory factor nNIF and NRPs Block NET formation in vitro and mouse models of infection and systemic inflammation, and show improved prognosis in these models [144] Inhibit excessive glycolysis PFKFB3 blockade 3PO Protect mice from acute lung injury via suppression of NF-κB-mediated vascular inflammation [77] PFK158 Suppress ATP production and proliferation in the mouse models of small cell lung cancer [149] Phenoxyindole 44…”
Section: Gsk484mentioning
confidence: 99%
“…75 A previous study demonstrated that NE, as one of the components of NET, participated in the proteolytic cleavage of some growth factors crucial for angiogenesis, such as VEGF and PDGF. 77 Ebos and Kerbel argued that the blockade of one growth factor could compensatorily upregulate the expression of others and stimulate angiogenesis again. 78 This could explain why the efficacy of anti-VEGF treatments varied among patients and resulted in only partial vessel regression.…”
Section: Neutrophils and Nets Induce A Pro-inflammatory And Pro-angio...mentioning
confidence: 99%
“…Stimulated by surgical stress like ischemia/reperfusion injury and inflammation, a meshwork of chromatin filaments is released from neutrophils to extracellular space and termed as neutrophil extracellular traps (NETs) 93 . Notably, in patients undergoing hepatic resection, increased NETs in the postoperative period were correlated with a > 4‐fold reduction in disease‐free survival while acceleration of tumor metastasis 21 .…”
Section: Tme Alternations After Surgery: Potential Triggers For Hcc R...mentioning
confidence: 99%
“…NETs are web-like structures formed by DNA fragments and proteins that can sequester CTCs. 16,17 In mice, surgery promoted NETs and micrometastasis. When mice were treated daily with DNAase after surgery, it reduced tumor growth.…”
Section: Perioperative Metastasis Formationmentioning
confidence: 99%